Assessing the relationship of psychological health with addiction to food. - Amaila Fazal; Khan, Saad Ahmed (International Journal of Endorsing Health Science Research, 2023)
Background: Food addiction is a behavioral addiction toward foods with high fat and sugar content that leads to overeating. In clinical practice, there is no diagnosis of addiction because diagnostic criteria focus on symptoms, distress, and impairment in daily functioning. Thus, this study aimed to assess the relationship of psychological health with addiction to food. Methodology: A self-administered questionnaire-based cross-sectional study was conducted on a total of 1200 participants aged between 15 and 60. The relationship between food addiction towards emotional and physical health was assessed using Yale Food Addiction Scale; items were rated and scored using a) a five-point Likert scale for assessing food addiction and b) a two-point scale used for assessing psychological health. Results: It was found that most of the participants had mild food addiction (66.5%). It was found that 65.5% of participants had mild psychological problems. When the food addiction was assessed in association with the demographic variable, a significant association was found for gender (P-value=0.009), BMI (P-value=0.024), lifestyle activity (P-value= 0.038), and family history (P-value=0.000). Conclusion: It was found that increased food addiction might lead to increased psychological problems.